Electrocatalytic Aspects of the Chlorate Process: A Voltammetric and DEMS Comparison of RuO2 and DSA Anodes. Issue 14 (19th October 2018) - Macounová, Kateřina Minhová; Simic, Nina; Ahlberg, Elisabet; Krtil, Petr
Abstract : The behavior of RuO2 and DSA anodes in hypochlorite oxidation is compared to outline limitations of the anode performance in the chlorate process. Both electrode materials oxidize hypochlorite via a radical involving mechanism, which produces overstoichiometric amounts of oxygen and hydrogen peroxide. Regardless of the electrode material the hypochlorite oxidation competes with chlorine evolution for the same surface sites. The hypochlorite oxidation prevails at low ionic strengths and in mildly alkaline media. On RuO2 based electrodes the electrochemical hypochlorite oxidation dominates, while on DSA the electrochemical hypochlorite oxidation is complemented by a catalytic decomposition of hypochlorite forming oxygen and hydrochloric acid. The catalytic hypochlorite decomposition observed for DSA represents a serious impediment for the chlorate process outlining the need of further optimization of the industrial grade anode for the chlorate process.